2011
DOI: 10.1002/jor.21470
|View full text |Cite
|
Sign up to set email alerts
|

In vivo strain analysis of the intact supraspinatus tendon by ultrasound speckles tracking imaging

Abstract: Limited data exist regarding why delaminated tears occur within the rotator cuff tendon, and no general agreement exists on how to handle this complicated tear. To analyze in vivo intratendinous strain of the supraspinatus tendon, the superficial, middle, and deep regions were marked with speckles using 2D speckle tracking echocardiography (2D STE) of 15 shoulders. The displacement and the strain of each speckle during isotonic and isometric shoulder motion were evaluated. Significantly different displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…1,9,19 Although earlier studies focused on tracking the cardiac organs or blood flow, speckle tracking studies have become widely used to estimate the displacement and strain of tendons or muscles. 12,13,20,22 Stegman et al demonstrated the efficacy and accuracy of 2D STE in estimating the displacement of the flexor digitorum superficialis (FDS) tendon. 22 They assessed the displacement of the FDS tendon using 2D STE at wrist level while a video microscope simultaneously imaged the exposed FDS tendon as a reference for validation during open carpal tunnel surgeries.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1,9,19 Although earlier studies focused on tracking the cardiac organs or blood flow, speckle tracking studies have become widely used to estimate the displacement and strain of tendons or muscles. 12,13,20,22 Stegman et al demonstrated the efficacy and accuracy of 2D STE in estimating the displacement of the flexor digitorum superficialis (FDS) tendon. 22 They assessed the displacement of the FDS tendon using 2D STE at wrist level while a video microscope simultaneously imaged the exposed FDS tendon as a reference for validation during open carpal tunnel surgeries.…”
Section: Discussionmentioning
confidence: 98%
“…Kim et al assessed not only the displacement but also the strain of the supraspinatus tendon using 2D STE. 12 They evaluated the in vivo strain of the intact supraspinatus tendon during isotonic and isometric shoulder motion. They demonstrated that interobserver and intraobserver reliability for isotonic strain measurement (r ¼ 0.78 and 0.81) was relatively lower than that for isometric strain measurement (r ¼ 0.88 and 0.90).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound elastography has been primarily utilized to quantify motion along the longitudinal axis of the tendon (Brown, Alsousou, Cooper, Thompson, & Noble, 2013; Farris et al, 2012; Farron, Varghese, & Thelen, 2009; Franz, Slane, Rasske, & Thelen, 2015; Kim, Kim, Bigliani, Kim, & Jung, 2011; Korstanje et al, 2012; Lichtwark & Wilson, 2006; Slane & Thelen, 2015; Yoshii et al, 2011). There is a lack of information on motion along the short axis of the tendon, which may have clinical implications for the treatment of insertional tendinopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical applications include assessing contractility and strain deficiencies in the myocardium and quantifying mechanical properties of tissue-engineered implants [26]–[31]. Several recent studies have implemented UEI to quantify the mechanical properties of human skeletal muscle and tendon (electrically stimulated or under load) [4], [32]–[40]. However, none of these studies employed elasticity imaging to quantify differences in tendon mechanical properties associated with degeneration or rehabilitation.…”
Section: Introductionmentioning
confidence: 99%